Pengembangan Pariwisata Digital Berbasis Komunitas di Desa Hargomulyo, Kabupaten Gunungkidul - Ludvianto, Meganusa (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
The tourism sector is promising to be developed in Indonesia, especially in the digital era. Group 77 KKN UAJY 79 gave an idea for tourism development in Hargomulyo Village, Gunungkidul. The idea is based on the potentials of Hargomulyo Village, then was linked to several concepts such as community based and one stop service tourism. Not only infrastructure and human resources, group 77 also directs development in Hargomulyo Village towards digital tourism. Thus, Hargomulyo Village will be ready to become a community based and digital tourism village with one stop service system to facilitate the focus of development.